The service sector in India's development - Nayyar, Gaurav 1981- (Cambridge University Press, 2012)
A striking aspect of India's recent growth has been the dynamism of its services sector. In 2010, it accounted for 57 percent of the country's GDP and 25 percent of its total employment. The results do not conform to the growth experience of currently industrialized countries or other developing economies. Is the increasing share of the service sector in India's total output simply notional, as several activities that were earlier classified in the industrial sector are now subsumed in services' value added, or because the relative price of services has increased over time? No. The sector's growth is real - it is linked to household final demand, policy reforms and increased service exports. Is this service-led growth process sustainable? That remains an open question because the service sector is highly heterogeneous, ranging from software services and business process outsourcing to wholesale and retail trade and personal services. These subsectors vary considerably in the context of different economic characteristics that are important for development
Title from publisher's bibliographic system (viewed on 05 Oct 2015)
Keywords: Service industries / India; Indien